2021
DOI: 10.1021/acs.inorgchem.0c03771
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Controlled Synthesis of Ultrathin Nickel Hydroxide Nanosheets for Electrocatalytic Oxygen Evolution

Abstract: The development of oxygen evolution reaction (OER) catalysts with high activity and high stability through convenient and economical methods is greatly important for the promotion of hydrogen energy based on electrolysis technology. Herein, by using an unconventional high electrodeposition potential, novel petal-like clusters constructed by cross-linking ultrathin nickel hydroxide nanosheets were controllably synthesized on nickel foam (or copper foam or carbon cloth) and the effect of electrodeposition condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…Hydrogen production from water splitting using renewable energies can be one of the efficient storage options. , Electrolytic water splitting includes the oxygen evolution reaction (OER) in the anode and the hydrogen evolution reaction (HER) in the cathode, , where the OER is kinetically unfavorable due to four electrons being needed to form oxygen–oxygen bonding. The role of the OER catalyst is thus essential to lessen the overpotential and fasten the water splitting. IrO 2 and RuO 2 have shown the highest OER activity in both acidic and alkaline electrolyte solutions, but the noble metal catalysts limit the commercialization due to the scarcity and high cost. Much research has thus focused on nonprecious metals, including Ni, Fe, Co, and Mo, as the alternatives. Among them, Ni hydroxides have shown active performance under alkaline OER conditions. …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen production from water splitting using renewable energies can be one of the efficient storage options. , Electrolytic water splitting includes the oxygen evolution reaction (OER) in the anode and the hydrogen evolution reaction (HER) in the cathode, , where the OER is kinetically unfavorable due to four electrons being needed to form oxygen–oxygen bonding. The role of the OER catalyst is thus essential to lessen the overpotential and fasten the water splitting. IrO 2 and RuO 2 have shown the highest OER activity in both acidic and alkaline electrolyte solutions, but the noble metal catalysts limit the commercialization due to the scarcity and high cost. Much research has thus focused on nonprecious metals, including Ni, Fe, Co, and Mo, as the alternatives. Among them, Ni hydroxides have shown active performance under alkaline OER conditions. …”
Section: Introductionmentioning
confidence: 99%
“…169,181 Fluoride-free approaches include cathodic deposition of nanostructured Ni deposit from the electrolyte containing Ni 2+ salts followed by anodic oxidation. 182 Recently, Wan et al 168 reported anodic oxidation of Ni foam in 1−10 M KOH at 1−3 A cm −2 for 3 h, where metal oxidation and oxygen evolution occur simultaneously to give a nanostructured electrode. Besides, oxidation of Ni mesh support was also observed during the long-term stability test.…”
Section: Key Parameters In Evaluating Catalyst Degradationmentioning
confidence: 99%
“…It was recently shown that electrodeposition parameters directly regulate the loading mass of Ni(OH) 2 , which directly influences the catalyst morphology. 182 In this way, the higher catalyst loading can in some cases repress the activity as the electrochemical active surface area decreases due to the thickening of the Ni(OH) 2 sheets. Thick deposits can also force the formation of NiO that passivates the Ni mesh anode.…”
Section: Key Parameters In Evaluating Catalyst Degradationmentioning
confidence: 99%
See 2 more Smart Citations